THERAPEUTIC POTENTIAL OF CYTOKINE-PRECONDITIONED HUMAN UMBILICAL CORD BLOOD DERIVED MESENCHYMAL STEM CELLS IN THE EXPERIMENTAL MODEL OF RHEUMATOID ARTHRITIS - Sarsenova, Madina (Nazarbayev University School of Medicine, 2024)
Rheumatoid arthritis (RA) is a persistent autoimmune condition primarily marked by the generation of autoantibodies. RA causes the gradual deterioration of joints due to the breakdown of cartilage and bone tissues, resulting in to a debilitating illness for the patient. Approximately 30% of instances result in people becoming incapacitated within the initial 10 years if the condition is unmanageable. The pathophysiology of RA is linked to the imbalance of both innate and adaptive immune responses. Currently, therapeutic practice is using traditional therapies such as steroid medications, antirheumatic medicines, and biological agents. These treatments have shown to be effective and provide a longer time of remission. Nevertheless, prolonged use of these medications leads to adverse reactions, and some individuals with RA may develop resistance to these therapies. Recent research has uncovered that mesenchymal stem cells (MSCs) have strong capabilities to regulate and suppress immune system activity. These cells possess significant potential for differentiation into several cell types, such as adipocytes, chondrocytes, and osteoblasts, among others. MSCs possess distinctive immunomodulatory features, in addition of their progenitor traits. The MSCs can adopt either a pro-inflammatory or anti-inflammatory phenotype, depending on the surrounding environment. Given this fact, we propose that the cell preconditioning technique with pro-inflammatory cytokines can be utilized to enhance the therapeutic effectiveness of MSCs in treating RA. This study aims to assess the immunomodulatory and immunosuppressive characteristics of MSCs in a laboratory setting. Furthermore, the impact of administering cytokine-preconditioned MSCs systemically will be evaluated in mice with collagen antibody induced arthritis. The study findings indicate that MSCs could be considered as a viable alternative for treating RA.
Keywords: Type of access: Embargo; mesenchymal stem cell; preconditioning; rheumatoid arthritis; cellular therapy